2022
DOI: 10.3389/fbioe.2022.939158
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Based Prussian Blue Nanocatalysts Suppress Non-Small Cell Lung Cancer Growth and Metastasis via Photothermal and Chemodynamic Therapy

Abstract: Based on the safety of prussian blue (PB) in biomedical application, we prepared manganese-based prussian blue (MnPB) nanocatalysts to achieve enhanced photothermal therapy and chemodynamic therapy. And we conducted a series of experiments to explore the therapeutic effects of MnPB nanoparticles (NPs) on non-small cell lung cancer (NSCLC) in vivo and in vitro. For in vitro experiments, the MnPB NPs suppressed growth of A549 cells by reactive oxygen species upregulation and near-infrared irradiation. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The results demonstrated that MMP2 and MMP9 decreased compared with the control group ( Figure 4C ). These results were consistent with the study published previously ( Fang et al, 2022 ). Overall, these results indicated that MnPB NPs could inhibit migration of PANC-1 cells.…”
Section: Resultssupporting
confidence: 94%
“…The results demonstrated that MMP2 and MMP9 decreased compared with the control group ( Figure 4C ). These results were consistent with the study published previously ( Fang et al, 2022 ). Overall, these results indicated that MnPB NPs could inhibit migration of PANC-1 cells.…”
Section: Resultssupporting
confidence: 94%
“…The η of PBCN was calculated to be 60.1% based on the cooling curve (Fig. 3e), which is superior to other PBNPs-based nanocomposites, such as CDs/PBNPs nanomaterials (30%), 26 MnPB NPs nanomaterials (27.8%), 11 and CaP&PB (40.2%). 28 The good photothermal stability was verified by exposing PBNC to an 808 nm laser for 5 min, followed by natural cooling to room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…7 PTT is a typical treatment that induces tumor cell apoptosis via a photothermal agent irradiated under NIR light to generate local high thermal energy. 8 Common photothermal agents include gold nanomaterials, 9 MoS 2 , 10 and graphene oxide et al, 11 which have disadvantages such as high cost, complex synthesis, and low photothermal conversion efficiency. In contrast, Prussian blue nanoparticles (PBNPs) have been widely applied in PTT because of their simple synthesis, good photothermal properties, and low cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…21 Prussian blue nanoparticles (PBs) show unique properties. 22,23 They can be synthesized in mild conditions and have an excellent light-to-heat conversion rate, which is an ideal carrier of Cy for PDT/PTT synergistic therapy. 24 In addition, due to its outstanding biocompatibility, PB has been approved by the FDA.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that co‐delivery of the Cy with the photothermal agent (PTA) NPs can achieve the combined PDT and PTT, which could activation by one NIR light irradiation and integrate more functions 21 . Prussian blue nanoparticles (PBs) show unique properties 22,23 . They can be synthesized in mild conditions and have an excellent light‐to‐heat conversion rate, which is an ideal carrier of Cy for PDT/PTT synergistic therapy 24 .…”
Section: Introductionmentioning
confidence: 99%